2018
DOI: 10.1108/bij-02-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring interdependencies of preferred supplier enablers

Abstract: Purpose The purpose of this paper is to analyze preferred supplier enablers (PSEs) and measure the interdependencies among themselves for enhancing preferred supplier relationship. Design/methodology/approach In the current study, an approach has been developed in which the significance of various PSEs was determined by applying Fuzzy Analytic Hierarchy Process (FAHP) and the prominent PSEs were screened out through Pareto analysis. Also, the interdependence among the prominent PSEs was measured by applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Therefore, confident, reliable and dependable suppliers bring a number of benefits to firms, including planning knowledge, as well as having a significant, effective and positive impact on delivery, the flexibility of operations and joint logistical activities. This will raise the level of confidence, reliance and cooperation for several functions and operations to reach a high level of sustainable performance (Routroy, 2018). Namagembe (2020) showed that suppliers' involvement with firms enhances firms' ability to compete by adopting and sharing different technologies such as keeping pace with technological development, applying better practices, developing new products together, The effect of supplier involvement reaching markets quickly, flexibility in responding to changing demands and finally, smoothing flows of materials with optimization of using resources.…”
Section: Sc Reliancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, confident, reliable and dependable suppliers bring a number of benefits to firms, including planning knowledge, as well as having a significant, effective and positive impact on delivery, the flexibility of operations and joint logistical activities. This will raise the level of confidence, reliance and cooperation for several functions and operations to reach a high level of sustainable performance (Routroy, 2018). Namagembe (2020) showed that suppliers' involvement with firms enhances firms' ability to compete by adopting and sharing different technologies such as keeping pace with technological development, applying better practices, developing new products together, The effect of supplier involvement reaching markets quickly, flexibility in responding to changing demands and finally, smoothing flows of materials with optimization of using resources.…”
Section: Sc Reliancementioning
confidence: 99%
“…Therefore, confident, reliable and dependable suppliers bring a number of benefits to firms, including planning knowledge, as well as having a significant, effective and positive impact on delivery, the flexibility of operations and joint logistical activities. This will raise the level of confidence, reliance and cooperation for several functions and operations to reach a high level of sustainable performance (Routroy, 2018).…”
Section: Theoretical Underpinning Research Model and Hypotheses Devel...mentioning
confidence: 99%
“…Similarly, from the buyer standpoint, SET suggests that the more a supplier is willing to share his technological competencies and preferentially allocate resources to his buyer, the more the latter is inclined to award him a preferred supplier status (Schiele, 2022). Buying firms award preferred supplier status to a partner based on the extent to which their interests are fulfilled and on the appropriateness of the suppliers' characteristics (C.V and Routroy, 2016, 2018). Preferred suppliers are strategic partners who are likely to offer buying firms a renewed product performance at an advantageous price, as well as privileged service support and resources (Halley and Nollet, 2002, Maestrini et al ., 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The challenge is the collaboration of the front end of the supply chain with its back end. Supply chain collaboration focuses on the communication of customers and suppliers (Routroy, 2018). According to stakeholder theory, customers and suppliers, as stakeholders, are able to influence the relationships along the supply chain.…”
Section: Environmental Sc Collaborationmentioning
confidence: 99%